PENGARUH KUALITAS PRODUK DAN LAYANAN TERHADAP KEPUASAN PELANGGAN UMKM MIE AYAM - Rian Azhar Ramadhan; Lailatul Azkia; Suhernah; Miftah Komala Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study examines the influence of product and service quality on customer satisfaction in Mie Ayam Mas Kalimin MSMEs, Banten. This research method uses a quantitative descriptive approach by processing data from direct observation of information provided by salespeople and customers. The results showed that product quality, which includes taste, cleanliness, and presentation, as well as service quality such as comfort and convenience, made a significant contribution to positive perception and customer loyalty. Despite facing various challenges due to the pandemic, MSMEs are able to survive while maintaining quality. The recommendation for MSME actors is to improve the quality of products and services through training and innovation. The results of this study support the theory that customer satisfaction increases along with expectations of products and services.